Estudio de Impacto Ambiental (Ex-Post) en el relleno sanitario de la ciudad de Catacocha, cantón Paltas - Carrión Soto, Carmen Yessenia (2023)
Local authorities face a challenge when it comes to managing solid waste at landfills, since poor management leads to environmental damage and social unrest. The purpose of this study was to identify the main environmental impacts caused by the operation of the Catacocha landfill, by conducting a baseline survey, identifying, assessing and evaluating impacts through the importance matrix, which considered both qualitative and quantitative assessments of impacted factors, their magnitude and intensity. The results according to the baseline reveal that the values obtained in the noise monitoring (88.5 dB and 75.7 dB) exceed the maximum permissible limits issued by the TULSMA and the WHO; the water quality of the well is contaminated, due to the ratio of BOD 5 / COD < 0.2; the health of the soil in the direct area is affected, there is a low and medium diversity in terms of flora and fauna respectively; all these factors cause harmful effects on the environment and people's health. The main negative impacts generated by the operation of the landfill are: air, soil, water, fauna and the inhabitants of the Ongonga neighborhood. It was necessary to develop an environmental management plan in the study area due to the significant impacts found there. Programs in this plan aim to reduce the effects of contamination, improve social development, and improve the quality of life for residents living near landfills.